1974
DOI: 10.1007/bf00011424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen on the incidence of Verticillium wilt disease of egg plant caused by Verticillium dahliae Kleb

Abstract: An investigation on the effect of different levels of nitrogen on the incidence of Verticillium wilt disease of egg plant was carried out. Application of nitrogen to the host increases susceptibility to Verticillium wilt disease. The initial s y m p t o m s of disease appeared on the 6th day in plants fertilized with 200 kg and 400 kg N/ha following inoculation of plants with Verticillium dahliae, whereas the appearance of s y m p t o m s was delayed to a period of a further two days in the plants supplied wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

1981
1981
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…However, most studies have been conducted in herbaceous crops. Several authors have reported that low nitrogen (N) levels provoke a reduction of the susceptibility to Verticillium wilts in lucerne [11], hop [12], eggplant [13] or hop [14]. On the contrary, high nitrogen content in situations of potassium (K) deficiency may cause an increase in disease severity [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies have been conducted in herbaceous crops. Several authors have reported that low nitrogen (N) levels provoke a reduction of the susceptibility to Verticillium wilts in lucerne [11], hop [12], eggplant [13] or hop [14]. On the contrary, high nitrogen content in situations of potassium (K) deficiency may cause an increase in disease severity [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies have been conducted in herbaceous crops. Several authors have reported that low nitrogen (N) levels reduce susceptibility to Verticillium wilts in lucerne [11], hop [12,13] and eggplant [14]. In contrast, high nitrogen content combined with potassium (K) deficiency may cause an increase in disease severity [9].…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ akkumulieren und wegen einer geringeren Biomasse der Pflanzen eine höhere Konzentration erreichen. Wenn auch wenig über die Nährstoffsituation in Verticillium-infizierten Pflanzen bekannt ist, so wurde doch der Einfluss von Nährstoffmangel oder -überschuss im Boden oder Medium auf Verticillium induzierte Symptome vielfach untersucht (Ashworth et al, 1985;Burge & Simmons, 1982;Kudela & Pirkl, 1978;Sivaprakasam & Rajagopa, 1974;Walker et al, 1954). Durch Kalken des Bodens konnte die Resistenz in Medicago sativa gegen V. albo atrum erhöht werden (Kudela & Pirkl, 1978).…”
Section: Abb 429unclassified
“…Bei Auberginen-bzw. Tomatenpflanzen führte die erhöhte Zugabe von Stickstoff, Kalium und Phosphor zu einer Verstärkung von Verticillium-induzierten Symptomen (Sivaprakasam & Rajagopa, 1974;Walker et al, 1954).…”
Section: Abb 429unclassified